Sakayan sang kabuhi the Buenavista-Iloilo sakayan trade, 1930s-2000s - Galanza, Duvisa, S.
This is a descriptive study of the Sakayan Trade that exists between Buenavista, a Municipality of Guimaras, and Iloilo. This study attempts to trace the origin and development of the Sakayan Trade. It also delves on the factors that contributed to the maintenace of the trade. This study also discusses the advantages brought by the Sakayan Trade to the Municipality of Buenavista., The Sakayan Trading between Buenavista and Iloilo can be traced back before the coming of the Spaniards in the town. When the Spaniards came to Guimaras headed by Gonzalo Ronquillo de Penalosa, they noticed that the town has very good fishing grounds and the natives have boats, which they use in fishing. The trade began to flourish after the construction of the Buenavista Wharf and the road from Sto. Rosario, where the port is located to Brgy. Supang, which was initiated by the Americans. From 1930s up to early 1940s, sailboats served the people of Buenavista and Iloilo. Though the trade is regular, it is quite slower because it depends upon the condition of wind and water. In 1948, the motor engine was introduced and this marked a change in the trading operation. The sakayan operation became faster and it is now convenient for passengers to travel. Passengers generally comprise the cargo of the Sakayan but it still carry cargoes like fruits, vegetables and other agricultural products. Today, the Sakayan Trade continues to be in operation. There are various factors that contributed to the maintenance of the trade. One factor is the abundant supply of raw materials. Buenavista, as one of the centers of boatmaking tradition, has plenty of woods such as kamonsil, lauaan, kamagong and kbi, which are very suitable in making sakayan. This craft made the trade possible. The presence of skilled carpenters called panday also accounts to the maintenance of the trade. These pandays made the boatmaking tradition survive up to this time and the boats they made allowed the goods and passengers to be transported to Iloilo and vise-versa. Another important factor is the development in cash crop production, which in turn increased the flow of agricultural products from Buenavista to Iloilo using Sakayan. The economic contribution of the trade in the municipality in terms of jobs and the opening of commercial opportunities also facilitated the trade between Buenavista and Iloilo. The increase in population of the municipality that led to higher mobility of the people necessitated the construction of boats and supported the trading relation. In addition, the demand for higher education increased the number of students plying to Iloilo using Sakayan. The geographical setting is also a contributing factor on the maintenace of the trade. The Sakayan trading relation has proved to be advantageous to the Municipality of Buenavista. These advantages can be categorized into two; The economic and the socio-cultural advantages. Economic advantages include the expansion of trade and commercial activities. Buenavista became on of the leading disbursing point of products. The trade facilitated the distribution of goods from Buenavista to Iloilo and vise-versa. The trade also resulted to the creation of more jobs such as being a sakayanon, pakyaw, tindera, balot vendor, vehicle drivers and opening of business opportunities like the establishment of food stalls and grocery stores that accomodate passengers, port personnel and sakayanons and give them an opportunity to earn income. The trade has played a great part on the development of Tourism industry. it exposed Buenavista, as a scenic and historic place, to the knowledge of people from other places. It also resulted to the conversion of lands into plantations, agricultrual and agro-industrila sites. On the other hand, scoio-cultural advantages include the expansion of social and cultural activities. Stringer family ties, love affairs were established and expanded the social interaction between people that were involved in the trade. It was also the trade that contributed to the improvement in social services and public faciltities. The trade necessitated the construction of port,, farm-to market roads, terminal buildings and streetlights. Through this trade, the perception of the people towards their environment was changed. They became more aware of the happenings in their environment and neighboring places such as Iloilo. They became updated of the latest news especially on the field of politics in western Visayan region. The notion that Guimarasnons are backward people was minimized, for they are now aware of the latest trends in fashion. Intermarriages between the people of Buenavista and those living in Iloilo is also one of the results of the trade. The boatmaking tradition also owed its continuance to the trade. It was trade that encourages the panday of the palce to construct Sakayan. Up to this time, the Buenavista-Iloilo Sakayan Trade continues to serve the people of the said places and keep on influencing th elives of the people of Buenavista in amy ways.